Retrospective Comparison of Efficacy and Safety of Rabbit Anti-Thymocyte Globulin and Porcine Anti-Lymphocyte Globulin in Patients With Acquired Aplastic Anemia Undergoing Hematopoietic Stem Cell Transplantation From Matched Sibling Donors - Zhang, Yuanfeng; Chen, Xin; Li, Lin; Li, Yun; Lin, Li; Cao, Yang; Wang, Na; Yang, Donglin; Pang, Aiming; Zhang, Rongli; Ma, Qiaoling; Zhai, Weihua; et al. (Frontiers in Immunology, 2022)
We compared the efficacy and safety of porcine anti-lymphocyte globulin (pALG) (n=140) and rabbit anti-thymocyte globulin (rATG) (n=86) in patients with acquired aplastic anemia (AA) receiving hematopoietic stem cell transplantation (HSCT) from matched sibling donors (MSD) in two transplantation centers in China. The groups had similar baseline characteristics except for a higher number of infused mononuclear cells (P<0.001) and a higher proportion of peripheral blood stem cells as graft sources (P=0.003) in the pALG group. The rates of neutrophil engraftment (P=1), platelet engraftment (P=0.228), bloodstream infection (P=0.867), invasive fungal diseases (P=0.362), cytomegalovirus viremia (P=0.667), and graft rejection (P=0.147) were similar in the two groups. A higher cumulative incidence of grade II-IV acute graft versus host disease (aGvHD) at 100 days occurred in the pALG group (19% vs. 8%, P=0.036) while no significant differences in grade III-IV aGvHD (P=0.572), mild to severe chronic GvHD (cGvHD) (P=0.181), and moderate to severe cGvHD (P=0.586) were observed. The actual 5-year overall survival (OS), failure-free survival (FFS), and GvHD-free, FFS rates of the pALG group were 87% (95% confidence interval [CI], 82-93), 85% (95% CI, 80-92), and 78% (95% CI, 72-92) versus 91% (95% CI, 86-99) (P=0.33), 88% (95% CI, 82-97) (P=0.367), and 79% (95% CI, 72-90) (P=0.824) in the rATG group, respectively. A busulfan-containing conditioning regimen was the only adverse risk factor for OS and FFS in multivariate analysis. In conclusion, pALG is an alternative to rATG in patients with severe AA receiving MSD-HSCT. A prospective, large-sample study is needed to explore this therapy further.